Selected measures to implement the employer’s obligation to counter mobbing. The role of Anti-Mobbing Committees in Light of Court Jurisprudence - Piątkowska, Paulina; Zychla, Agnieszka (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
The study focuses on the issue of anti-mobbing proceedings. In this text, the Anti-Mobbing Committee was taken under the microscope in the light of jurisprudence. It is a special body because its members are selected by the employer, who may also turn out to be a mobber. This is controversial due to the possible lack of objectivity. The authors also noted that the anti-mobbing procedure itself is not widespread among employees, and it is the employer’s duty to define it. The paper also draws attention to e.g., for allowing the need to share protocols of specific proceedings of the Anti-mobbing Committee or its responsibility for tasks in situations where it was appointed by the employer. After analyzing the jurisprudence, the authors come to various conclusions and emphasize the importance of the existence of the Anti-Mobbing Committee and some aspects related to it, both with the committee itself and its role in the above-mentioned procedure.